Modern Paradigms of Legal Understanding and the Development of Legal Consciousness in Supply Chain (Case Study of Russia) - Nesmeyanova, Svetlana E.; Ryabova, Tatiana V.; Tkhabisimova, Lyudmila A.; Tsapko, Maxim I.; Makogon, Boris V. (International Journal of Supply Chain Management, 2018)
This paper deals with the problem of the development of legal consciousness in supply chain of modern Russia amid the conceptual crisis of legal understanding in Russian law. The objective of the presented paper is to analyze modern paradigms of legal understanding and vectors of their development, as well as the influence of legal understanding on the development of legal consciousness in supply chain of Russia. The authors consider the current state of legal awareness in Russia. The choice of the topic is due to the existing theoretical discussion on the relationship between law, society and the state in supply chain of Russia.